Inovasi Guru Membuat Musik Menggunakan Gelas Berisi Air Dalam Pembelajaran Seni Musik Untuk Siswa Kelas Rendah Sekolah Dasar di SDN Harjosari Lor 01 - Fujiyati, Indah; Andaryani, Eka Titi (Jurnal Ilmiah Profesi Pendidikan, 2024)
Teacher innovation is needed in the learning process to support the quality of education. The purpose of this study was to analyze the innovations made by teachers in learning the art of music for elementary school students. In this study used a descriptive qualitative method, where 32 informants were involved in data collection, consisting of 1 class teacher, and 31 students of SDN Harjosari Lor 01. Data collection is done through observation, interviews, and documentation. The Miels and Huberman models were used in data analysis. The results of the study show that the teacher's innovation in teaching the art of music for low grade students is carried out by utilizing the tools that are around the child. This tool is created into learning media used by students. Innovations carried out by the teacher have a positive influence on children's daily assessments, which consist of assessing attitudes, assessing knowledge, and assessing skills.